Metastatic melanoma with dedifferentiation and extensive rhabdomyosarcomatous heterologous component. (1st March 2018) - Campbell, Katelynn; Kumarapeli, Asangi R.; Gokden, Neriman; Cox, Roni M.; Hutchins, Laura; Gardner, Jerad M.
Abstract : Melanoma may undergo dedifferentiation and sarcomatous transformation with loss of melanocytic markers. Dedifferentiated melanoma rarely forms true rhabdomyoblasts with skeletal muscle immunophenotype (rhabdomyosarcomatous heterologous component). A 52‐year‐old woman was diagnosed with invasive melanoma (Breslow thickness 0.83 mm) of the upper back in 2012, treated by wide local excision only. In 2013, an axillary mass was excised to show metastatic melanoma with 2 morphologies: an epithelioid morphology expressing S100 and MART‐1 and a spindled morphology with loss of melanocytic markers but strong expression of desmin. This metastasis was found to have BRAF V600E mutation. In 2015, a thoracic epidural mass biopsy showed atypical spindle cells with focal HMB‐45 but essentially no S100 expression. Numerous rhabdomyoblasts, some with striations that were strongly positive for desmin and myogenin, were present. In 2016, a right nephrectomy was performed for metastasis to the kidney, and showed sheets of spindle cells and rhabdomyoblasts expressing desmin and myogenin but not S100. Only focal areas demonstrated expression of HMB‐45 and SOX‐10, supporting the melanocytic origin of the tumor. The numerous rhabdomyoblasts and the loss of S100 expression in the metastatic lesions in this case could have easily led to misdiagnosis if the clinical history was not known.